Diagnostic accuracy of ultrasound for small bowel obstruction: A systematic review and meta-analysis. Issue 136 (March 2021) - Lin, You-Cheng; Yu, Yi-Chung; Huang, Yu-Ting; Wu, Yun-Yu; Wang, Ting-Cheng; Huang, Wen-Cheng; Yang, Meng-Duo; Hsu, Yuan-Pin
Highlights: The evidence of using ultrasound to diagnose SBO remains inconclusive. The result indicates that ultrasound has an overall sensitivity of 92 % (95 % CI: 89%–95%) and specificity of 93 % (95 % CI: 85%–97%) to diagnose SBO. However, the specificity is significantly lower when an ultrasound is performed in North America, and in the emergency department. Additionally, the specificity is significantly lower when computed tomography is used as the only reference standard. Therefore, ultrasound should be cautiously used to rule in SBO in different situations. Abstract: Purpose: Accurate diagnosis of small bowel obstruction (SBO) remains challenging. The evidence of the diagnostic accuracy of ultrasound varies among studies, with reporting sensitivity ranging from 82 % to 100 % and specificity ranging from 54 % to 100 %. The aim of our study is to perform a systematic review and meta-analysis to investigate the accuracy of ultrasound for diagnosing SBO. Method: The PubMed, EMBASE, Cochrane Library, Web of Science, and Scopus databases were searched from database inception to March 2020. Randomized controlled trials, quasi randomized studies, and prospective or retrospective cohort studies that evaluated the diagnostic performance of ultrasound for the diagnosis of bowel obstruction in adult patients (age ≥ 16 years) were eligible. The QUADAS-2 tool was used to assess the quality of the included studies. The pooled sensitivities, specificities were analyzed using a bivariate random-effects model. (PROSPERO ID: CRD42020170010). Results: Fifteen studies, with most rating as a moderate risk of bias, met the inclusion criteria. The pooled sensitivity and specificity were 92 % (95 % CI: 89%–95%) and 93 % (95 % CI: 85%–97%), respectively. Subgroup analysis revealed no significant differences in sensitivity when ultrasound was performed on different continents, in different settings, and under different reference standards. However, the specificity was significantly lower when ultrasound was performed in the North America, in the emergency department, and when computed tomography was used as the only reference standard. Conclusions: Overall, ultrasound is a highly sensitive and specific tool for the diagnosis of SBO. Using ultrasound to rule in patients with SBO should be used with caution, as variations in the specificity were observed in different study setting, operators from different continents and reference standards used.